IMPLEMENTATION OF SERVICE QUALITY TO CUSTOMERS AT PT GAPURA ANGKASA - Pratama Putra Pinatih, I Putu Arya; Abiyasa, Agus Putu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The Job Training Report (PKL) made by the author explains how the authors follow the activities at PT. Gapura Angkasa, Denpasar Branch for 2 months from July 4, 2022, to September 2, 2022. The author was placed in the Human Resource Development division, assisting in the field of student administration in carrying out On Job Training, training, and education staff, as well as assisting in the field of managing employee administration. Activity that is often done by the author is in entering the existing training data. The author wants to know how the HRD flow in developing career employees and the development of a quality workforce. The author gets various sciences and knowledge during the implementation of fieldwork practices, the author also acquires soft skills & hard skills that can be applied both in the real world of work and in everyday life.